Membumikan Teori Negara Kesejahteraan Dalam Penguatan Dana Desa Untuk Pengentasan Kemiskinan Menurut Keadilan Distributif - Arifin, Muhammad Zainul; Nugraha, Muslim; Yunithia Putri, Taufani; Ramadhan, Muhammad Syahri (Journal Of Law And Social Society, 2024)
Prosperity and welfare have been ideals pursued by the founders of this nation and the current Indonesian government. These ideals are manifested in the preamble of the 1945 Constitution, which states: "The government shall protect the entire nation and all the blood spilled, promote general welfare, and educate the life of the nation." However, in reality, the issue of social inequality in Indonesia has become increasingly acute. According to data released by the Central Statistics Agency (BPS) in March 2024, the poverty line is defined as an income of Rp. 536,122 per person per month, with 25.22 million people recorded as living below this threshold. Meanwhile, the World Bank's poverty standard is defined as a minimum daily income of $2.15 or approximately Rp. 970,000 per month. There is a significant discrepancy between the standard set by the Indonesian government and that of the World Bank, which presents a serious issue that must be addressed. In 2014, Law No. 6 of 2014 concerning Villages provided a legal foundation and strategic framework for the development and empowerment of village communities. Through authority in village governance, development implementation, community guidance, and empowerment, it is hoped that villages will develop awareness and initiative. Subsequently, the central government initial village fund transfers through the state budget (APBN), allocating 10% of the total funds outside of regional transfers (on top), implemented gradually. The increase in budget allocation disbursed to villages aims to support village development to enhance community welfare and improve the quality of life while addressing poverty. This is achieved by fulfilling basic needs, constructing village infrastructure, developing local economic potential, and sustainably utilizing natural and environmental resources. Thus, the author formulates the following research problems: How can the concept of a welfare state be reformulated as a strategy for poverty alleviation through the utilization of village funds in Indonesia? What concrete measures can be taken to ensure effective and targeted use of village funds for poverty alleviation in Indonesia? This research employs a normative legal study approach supported by empirical data. The theoretical framework includes the theory of the welfare state, the theory of legal development, and Jeremy Bentham's theory of economic analysis of law